The degree of using digital learning resources to improve self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies - Nouf Abdulrahman Alsamari; Abdelraouf Mohamed Ismail (International Journal of Computers and Informatics, 2024)
The study aimed to determine the degree of using digital learning resources to improve self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies. The study employed the descriptive survey method, by applying a questionnaire to a simple random sample consisting of (43) male and female students from the Department of Educational Media and Technology at the Arab East College for Graduate Studies. The study’s objectives focused on answering the following questions: What is the degree of using digital learning resources in the courses of the Department of Educational Media and Technology at the Arab East College for Graduate Studies? What is the level of self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies? What is the degree of using digital learning resources in improving self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies? The study results showed that the degree of using digital learning resources in the courses of the Department of Educational Media and Technology at the Arab East College for Graduate Studies was high, and the level of self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies was high as well. Moreover, the degree of using digital learning resources in improving self-learning among students of the Department of Educational Media and Technology at the Arab East College for Graduate Studies was very high. The research project concluded with a set of recommendations and research proposals that had an impact on enhancing the results reached by the research project and were expected to be a source of benefit in the field of specialization according to the topics addressed by the research project and related to digital learning resources, self-learning, and scientific research.